Learning conversations in museums - Leinhardt, Gaea; Crowley, Kevin; Knutson, Karen (Lawrence Erlbaum, 2002)
What do people learn from visiting museums and how do they learn it? The editors approach this question by focusing on conversations as both the process and the outcome of museum learning. People do not come to museums to talk, but they often do talk. This talk can drift from discussions of managing the visit, to remembrances of family members and friends not present, to close analyses of particular objects or displays. This volume explores how these conversations reflect and change a visitor's identity, discipline-specific knowledge, and engagement with an informal learning environment that h.